Use of natural rubber latex in road construction - Fernando M J; Nadarajah M (Rubber Mitram, 2001)
Latex is the most effective form of natural rubber for road construction, both centrifuged latex and revertex being used. The authors found creamed skim latex most effective for road-making. Because of its easy availability, however, field latex is more suitable for road-making in the natural rubber producing countries. Results of laboratory studies concerned the dispersion of rubber particles, temperature-dependent and rheological properties, ageing and stripping of rubberized bitumen and uses of rubber in mix designs. Experimental stretches of road surfacing have been laid with bitumen containing upto 4;field latex. Further test stretches are being laid with rubber-modified pre-mix using field and creamed skim latices.
Keywords: Bitumen; NR latex; Road construction; Road rubberization